Identification of patients with smouldering multiple myeloma at ultra‐high risk of progression using serum parameters: the Czech Myeloma Group model. (12th March 2020) - Hájek, Roman; Sandecka, Viera; Špička, Ivan; Raab, Marc; Goldschmidt, Hartmut; Beck, Susanne; Minařík, Jiří; Pavlíček, Petr; Radocha, Jakub; Heindorfer, Adriana; Jelínek, Tomáš; Stejskal, Lukáš; et al.
Summary: Smouldering multiple myeloma (SMM) presents without MM defining symptoms. We aimed to identify patients with SMM with an 80% risk of progression within 2 years using only serum parameters. In total, 527 patients with SMM were included and divided into a training group (287 patients from the Czech Myeloma Group [CMG]) and an independent validation group (240 patients from Heidelberg). The median follow‐up was 2·4 and 2·5 years, respectively. Progression to MM occurred in 51·9% of the CMG and 38·8% of the Heidelberg patients, respectively. The median risk of progression was 11·0% (CMG) and 9·7% (Heidelberg) per year, during the 5 years after diagnosis. A serum involved/uninvolved free light‐chain ratio of >30, immunoparesis, and serum monoclonal (M) protein of ≥2·3 g/dl emerged as powerful predictors of 2‐year progression rate with a hazard ratio (HR) of 2·49 (95% confidence interval [CI] 1·49–4·17), HR of 2·01 (95% CI 1·36–2·96) and HR of 2·00 (95% CI 1·44–2·79) ( P  < 0·001) in univariate Cox regression analysis, respectively. Based on this, the CMG model identified patients with SMM with a 2‐year risk of progression of 78·7% (95% CI 53·1–95·7; HR 6·8; P  < 0·001, CMG) and 81·3% (95% CI 47·1–98·8; HR 38·63; P  < 0·001, Heidelberg). Serum parameters in the CMG model allow identification of patients with SMM with an 80% risk of progression to symptomatic MM within 2 years.